Kick-ass: the new girl, volume 1 ebook - Millar, Mark (Kick-Ass: The New Girl, 2018)
KICK-ASS IS BACK ready to wipe out the city's criminal lowlives, destroy its gangs, and save its communities from decay. But there's a new face beneath the old mask, a new figure wearing that famous green and yellow spandex. Who is this new vigilante superhero? Who can fill Dave Lizewski's shoes? WHO IS THE NEW KICK-ASS? Find out in the first collection of KICK-ASS: THE NEW GIRL. MARK MILLAR and JOHN ROMITA, JR. reunite for the next chapter of the greatest superhero comic of all time. Collects KICK-ASS: THE NEW GIRL #1-6. Author: Mark Millar. Illustrator: John Romita Jr. . 2018 Dave and Eggsy Ltd. and John S Romita.